Dimensions of Ethics and Telemedicine in Indonesia: Enough of Permenkes Number 20 Year 2019 As a Frame of Telemedicine Practices in Indonesia? - Carolina Kuntardjo (SOEPRA, 2020)
Telemedisin in Indonesia was known a few years ago but unfortunately did not make progress in its implementation. As technology developed during the Industrial Revolution 4.0 era, Indonesia returned to pay attention to the telemedicine system. One manifestation is the enactment of Minister of Health Regulation No. 20 of 2019 concerning the Implementation of Telemedicine Between Health Service Facilities. In the preamble of this Permenkes, it appears that the spirit of doing telemedicine is in order to bring health services closer and improve the quality of health services in health facilities in remote areas that prioritize patient interests and safety. Despite the fact that telemedicine currently available in Indonesia is more personal between doctors and patients. Of course, this can be considered to violate existing regulations, because there are no rules that frame them. In addition to the benefits derived from telemedicine because health services for remote areas are increasingly affordable and faster, there are still many obstacles in terms of ethics and law. In legal matters, the lack of rules that frame the implementation of telemedicine can jeopardize the position of doctors in the event of a medical dispute. In terms of ethics, there are still a number of things that are not in accordance with the principles of bioethics, namely beneficence, non-maleficence, autonomy, and justice. It is feared that the doctor-patient relationship will fade in telemedicine. The doctor's professional standard is also the case, because a doctor may not be able to conduct a direct examination of patients. There are still many obstacles in the implementation of telemedicine that this should be a challenge for the Indonesian government through the Ministry of Health to pay more attention and make clearer rules to frame the implementation of telemedicine in Indonesia.